TRADITIONAL BALLO/TUAK BEVERAGE AS A PHENOMENON OF ALCOHOLIC DRINKS IN SOCIETY: Analysis of Social Impact and Sharia Maqashid Perspective - Siti Amalia; Firman Muh. Arif; Thayyib Kaddase (Jurnal Ilmiah Advokasi, 2024)
This research aims to identify the factors driving the residents of Kadong-Kadong Village to consume ballo. Additionally, the study aims to analyze community responses and government policies regarding the phenomenon of ballo consumption in the area using the perspective of Maqashid al-Syariah. The research methodology employed is a qualitative approach or field research with an exploratory nature. Legal, sociological, and normative approaches serve as the analytical foundation. Data collection involves observation, in-depth interviews, and documentary studies. The results indicate that the primary reasons for the residents of Kadong-Kadong Village, Bajo Barat Subdistrict, Luwu Regency, consuming ballo are to alleviate stress and influenced by their environment and social interactions. Community responses to this phenomenon are characterized by concern, and the village government has issued warnings about the dangers of ballo consumption, although there is currently no binding village regulation to address this issue. The phenomenon of ballo consumption in Kadong-Kadong Village is identified as conflicting with the concept of Maqashid al-Syariah, particularly in aspects related to preserving religion, life, intellect, lineage, and wealth. The implications of this research suggest that this phenomenon may jeopardize the well-being of the community, which should be safeguarded by Islamic law for the benefit of both the present and the hereafter.Keywords: Alcohol consumption phenomenon, Ballo/tuak beverage, Maqashid al-Syariah.